2004
DOI: 10.1038/sj.tpj.6500275
|View full text |Cite
|
Sign up to set email alerts
|

Combined actions of zinc and fluoxetine on nicotinic acetylcholine receptors

Abstract: Zinc and nicotinic acetylcholine receptors (nAChRs) seem to be associated with major depression, and some antidepressants, including fluoxetine (Prozac), antagonize nAChRs. Therefore, a study was made of the modulation of neuronal a4b4 and muscle a1b1gd nAChRs, expressing in oocytes, by the combined action of zinc and fluoxetine. At a holding potential of -60 mV, 200 mM zinc increased by 361% the currents elicited by acetylcholine (ACh currents) for a4b4 and by 182% for a1b1gd nAChRs. In contrast, 5 mM fluoxet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…In this regard, antidepressants normalize Zn 2þ levels in depressed patients. The evidence indicating that Zn 2þ potentiates the inhibitory action of fluoxetine on a4b4 and a1b1gd AChRs (García-Colunga et al, 2004) concurs with the results from animal and depressed patient studies (Cunha et al, 2008;Siwek et al, 2009;reviewed in Szewczyk et al, 2008). Considering the hypothesis that hyperstimulation of the cholinergic system over the noradrenergic system results in depressed states (Shytle et al, 2002b;Arias, 2009Arias, , 2010b, the observed inhibitory synergism by Zn 2þ and antidepressants could be of clinical significance.…”
Section: Positive Allosteric Modulatorssupporting
confidence: 65%
“…In this regard, antidepressants normalize Zn 2þ levels in depressed patients. The evidence indicating that Zn 2þ potentiates the inhibitory action of fluoxetine on a4b4 and a1b1gd AChRs (García-Colunga et al, 2004) concurs with the results from animal and depressed patient studies (Cunha et al, 2008;Siwek et al, 2009;reviewed in Szewczyk et al, 2008). Considering the hypothesis that hyperstimulation of the cholinergic system over the noradrenergic system results in depressed states (Shytle et al, 2002b;Arias, 2009Arias, , 2010b, the observed inhibitory synergism by Zn 2þ and antidepressants could be of clinical significance.…”
Section: Positive Allosteric Modulatorssupporting
confidence: 65%
“…, 2004; Yeung et al. , 1999), and numerous neurotransmitter receptor targets, including the nicotinic ACh receptor (García‐Colunga et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fluoxetine (1–10 μM) has direct off-target effects at nicotinic acetylcholine 212,213 and 5-HT3 receptors 214216 as well as diverse Cl − 217 , voltage-gated Ca 2+ and K + channels 218–223 . Importantly, therapeutically relevant concentrations of fluoxetine and its metabolite norfluoxetine act as potent positive allosteric modulators of GABA A Rs in vitro when tested on receptors expressed in heterologous cells 224 and in cultured neurons 225 .…”
Section: Pharmacologic Evidence In Support Of a Role Of Gabaergictranmentioning
confidence: 99%